The production of talk shows on Spanish public television (1990-2010): omnipresent content on TVE - Diego, Patricia (2021)
The talk show is an omnipresent genre on television schedules, although not the most successful with regard to ratings. This article rebuilds the recent history of its production on Televisión Española and analyzes its main features as a genre following an inductive research methodology. In conclusion the talk show has a great capacity for hybridization and adaptation as it can be found in all kinds of programs and diverse genres. Although there are no great differences between talk shows produced by private channels and the public broadcaster, given its commercial foundations, TVE has opted to a greater extent for formulas such as interviews and debates, and to a lesser extent for testimonial TV shows.